Analysis of the deglutition parameters in patients with dysphagia after speech therapy and nutritional support (Research, Society and Development, 2020)
Dysphagia is a change in swallowing that can be caused by underlying diseases that lead to structural and functional changes or by inappropriate habits of the individual when eating. This condition can lead to a great compromise in the patient's quality of life, which may result in future feeding through alternative routes, as well as being associated with bronchial aspiration and malnutrition. Therefore, it is evident the need to study the evolution of these patients through fiberoptic endoscopic examination of swallowing (FESS) after phonotherapy and nutritional support. Thus, a retrospective analysis of patients with FESS was performed before and after support by speech therapy and nutritional therapy to characterize posterior escape, Yale Classification, Penetration and Aspiration. The research resulted from an evaluation of 16 patients, in which 37.5% were observed after treatment with normal swallowing or with reduced amount of waste. The maintenance of the parameters evaluated between the two FESS were the most prevalent findings in most of the analyzed variables. Thus, therapy could indicate a potential stabilizer of patients' dysphagic evolution.